2017
DOI: 10.17116/jnevro20171171024-10
|View full text |Cite
|
Sign up to set email alerts
|

The association of intrathecal production of immunoglobulin free light chains and progression of multiple sclerosis

Abstract: Concentrations of kappa FLC can help to define the prognosis of MS early at the disease course. Although low concentrations of FLC do not exclude a severe disease phenotype, patients with high K-FLC concentrations are at greater risk for faster MS progression, probably, due to impaired reparation of neural tissue. Measurement of FLC concentrations can be used to determine a therapeutic tactics in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…To further investigate the role of KFLC as a prognostic biomarker in CIS patients, studies with longer follow-up duration are needed. The mean follow-up time of the studies included in this review was only 35 months (min-max: 24-58 months) [43,50,53,55,58,61,68,69,73,[82][83][84]86,87,130]. Furthermore, the knowledge about KFLC in other neurologic diseases with intrathecal inflammation is rare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To further investigate the role of KFLC as a prognostic biomarker in CIS patients, studies with longer follow-up duration are needed. The mean follow-up time of the studies included in this review was only 35 months (min-max: 24-58 months) [43,50,53,55,58,61,68,69,73,[82][83][84]86,87,130]. Furthermore, the knowledge about KFLC in other neurologic diseases with intrathecal inflammation is rare.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies denied a correlation between disease progression evaluated by EDSS and KFLC CSF concentration or KFLC indices [43,66,69,77,84,87]. In some studies, high KFLC CSF concentrations or KFLC indices were associated with a higher risk for CIS patients to be later diagnosed with definite MS [43,50,53,54,61,68,69,73,82,83,86,130]. In other studies, this correlation could not have been observed, and CIS patients with conversion to MS did not reveal elevated CSF KFLC [55,84,87].…”
Section: Correlation Of Flc With Brain Mri and Disability Progression In Msmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, an excess of KFLC-index has been associated with a higher probability of CIS conversion to MS (9), and patients with KFLC-index >100 at baseline had twice as high a probability of a second clinical attack within 12 months (27). Patients with higher baseline values of KFLC achieved EDSSconfirmed progression in shorter periods and showed a significant positive correlation with disability at follow-up, independently of the effects of age, OCB status at baseline, and DMT exposure (18,(28)(29)(30). Our conclusions should be interpreted cautiously due to study limitations such as low sample size, the low incidence in prognostic endpoints, and higher incidence of OCMBs as compared to other studies that might have introduced potential sources of bias.…”
Section: Discussionmentioning
confidence: 98%